Enforcement of Copyright Law on Non-Fungible Token (NFT) Through Smart Contracts - Deslaely Putranti; Uni Tsulasi Putri (Universitas Muhammadiyah Purwokerto, 2024)
The emergence of the Non-Fungible Token (NFT) was driven by the transformation of the digital world. NFT is now an investment option for the majority of investors. NFT is a digital asset that defines original artworks, such as a painting, drawing, piece of music, or in-game item, and is maintained in a blockchain-based ledger where the purchasing and selling process is conducted using cryptocurrency. As a form of copyright protection, the presence of NFT as a digital asset is fraught with complications. Digitizing an artwork that is subsequently converted to NFT infringes the original creator's copyright since someone may produce a digital version of another's work without their consent. The existing laws and regulations are yet to govern the ownership of NFTs that infringe the copyrights of others; thus, a solution is required, one of which is by the use of smart contracts. This is normative-juridical research, namely study undertaken by reviewing library resources or secondary sources. This study came into the conclusion that with the present state of technology, smart contracts cannot identify Copyright mistakes that are translated to NFT. Through human intervention, the blockchain network requires the addition of new applications.Keywords: Non-Fungible Token, Copyright, Smart Contract